Transdisciplinarity in Old and New Concepts for Novel Physiotherapies - Ciobanu, Adela-Madgalena; Riga, Sorin; Riga, Dan (Highlights on Medicine and Medical Research Vol. 7, 2021)
This book chapter deals with Transdisciplinarity in Old and New Concepts for Novel Physiotherapies.